The effect of CEO stock-based compensation on pricing of future earnings - CHOI, Bobae (Institutional Knowledge at Singapore Management University, 2016)
This paper examines whether CEO stock-based compensation has an effect on the market’s ability to predict future earnings. When stock-based compensation motivates managers to share their private information with shareholders, it will expedite the pricing of future earnings in current stock prices. In contrast, when equity-compensated managers attempt to temporarily manipulate the stock price to maximize their own benefit rather than that of shareholders, the market may not fully anticipate future performance. We find that a CEO’s stock-based compensation strengthens the association between current returns and future earnings, indicating that more information about future earnings is reflected in current stock prices. In addition, we find that the positive effect is weaker for firms that have a high level of signed discretionary accruals or a low management forecast frequency. Overall, our study suggests that on average, equity-based compensation improves the informativeness of stock prices about future earnings, while opportunistic discretionary accruals or lowered earnings guidance hamper this improvement.